Seismic reflection data support episodic and simultaneous growth of the Tibetan Plateau since 25 Myr - Jiang, X.; Li, Zheng-Xiang (Macmillan Publishers Limited, 2014)
The spectacular topography of the Tibetan Plateau is the result of collision between India and Eurasia over some 50 Myr, but how the plateau grew to its present size remains a topic of debate. Work along its eastern margin suggests a two-stage uplift (thus growth of the plateau) since 30–25 Myr. Here we report high-resolution seismic reflection and drill core results from the southern Tarim Basin that indicate a similar pattern for the northern margin of the plateau. The data suggest that uplift in northern Tibet started at ~23 Myr from near sea level, with the first episode finished by ~10 Myr, followed by a post-5-Myr episode of rapid uplift along the present plateau margin. The growth of the Tibetan Plateau after the Eocene thus appears to have been episodic in nature, and near-synchronous along both eastern and northern margins.